Strategi Negosiasi Perempuan Buruh Tani Padi dalam Peran Domestik dan Publik di Desa Kanor Kabupaten Bojonegoro - Aslamya, Zuhaeratul; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2024)
A rice farm worker is someone who works in the agricultural sector by cultivating, cleaning or harvesting land in accordance with the directions of the rice field owner. In a patriarchal culture, women have absolute responsibility for their domestic roles, while men have full responsibility for their public roles. In recent times, many women have entered public roles. This is because there are many needs that must be met. As financial managers, many women believe that the income provided by their husbands is not enough to meet their family's living needs. The aim of this research is to describe the negotiation process carried out and the negotiation strategies of women rice farming workers in domestic and public roles in Kanor Village, Bojonegoro Regency. The data collection technique in this research used in-depth interviews. The data analysis technique uses Miles and Huberman analysis through the stages of data reduction, data presentation and drawing conclusions. The research results show that the strategy chosen by female farm workers is an integrative negotiation strategy which takes the form of a strategy of choosing the right time and seduction. The seduction used is divided into three methods, namely: (1) using soft speech; (2) using special treatment; (3) Using sweet words to persuade. Then, in the negotiation process, household needs and work fatigue become the main problems and there is conflict due to differences of opinion. In the negotiation process the domestic roles being negotiated were: (1) Cooking; (2) Sweep; (3) Washing clothes. Meanwhile, the public negotiation process includes working hours as a farm worker and work permits as a rice farm worker until leaving the village.